Origins of harvested American black ducks: stable isotopes support the flyover hypothesis. Issue 1 (31st October 2022) - Kusack, Jackson W.; Tozer, Douglas C.; Schummer, Michael L.; Hobson, Keith A.
Abstract: Waterfowl management is more effective when based on detailed information on population connectivity between breeding, wintering, and stopover sites. For the American black duck ( Anas rubripes ), a species of conservation concern, estimates for the fall age ratio at harvest differed depending on whether harvest data were derived from Canada or the United States, suggesting regional differences. Within Canada, hunters in Atlantic Canada were more likely to harvest black ducks from nearby breeding locations compared to hunters in southern Ontario and Quebec, Canada, who were more likely to harvest individuals from the Boreal Softwood and Taiga Shield of eastern Canada. Black ducks harvested in the United States are thought to originate predominantly from northern portions of the breeding range, leading to the flyover hypothesis, which postulates that black ducks produced in the Boreal Softwood and Taiga Shield region are less susceptible to harvest by hunters in Atlantic Canada and northeastern United States. To test the flyover hypothesis, we examined regional and temporal differences in the origins of harvested black ducks using feathers from wings ( n  = 664) submitted by hunters to the species composition and parts collection surveys across 3 hunting seasons (2017–2018, 2018–2019, 2019–2020). We used a likelihood‐based assignment method that relied on feather stable‐hydrogen isotopes ( δ 2 H) and stable‐carbon isotopes ( δ 13 C) to determine the natal or molt origin of individuals harvested within eastern Canada and the United States. We also used a spatial clustering technique to group harvested individuals by area of origin without a priori knowledge of such regions. Adult female black ducks originated farther south compared to males and juveniles. All sexes and ages of black ducks harvested in Atlantic Canada showed predominantly southern origins, while those harvested in the United States and other Canadian provinces primarily originated farther north within the boreal, supporting the flyover hypothesis. By contrast, we found no relationship between timing of harvest or peaks of migration and individual origin. After combining band returns and stable isotopes, we inferred 2 distinct stocks: the Mississippi flyway stock and the Atlantic flyway stock. We recommend that regional demographic parameters, particularly for Atlantic Canada, be directly measured to promote more effective conservation of black ducks and optimize harvest opportunities in the United States and Canada. Abstract : The flyover hypothesis proposes that American black ducks harvested in Atlantic Canada originate from nearby breeding locations, in the south, while those harvested in the USA and elsewhere in Canada are thought to originate from farther north in the boreal. We examined regional differences in the origins of harvested ducks using stable isotopes within feathers and found that ducks harvested in Atlantic Canada showed predominantly southern origins, while those harvested elsewhere primarily originated farther north.